PENGARUH LATIHAN SIRKUIT TRAINING TERHADAP KECEPATAN LARI 100 METER PADA MAHASISWA FIK UNM - Kasmauati Kasmauati; Andi Atssam Mappanyukki; Wahyudin Wahyudin; Nur Indah Atifah Anwar (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
The formulation of the problem in this research is what is the effect of implementing circuit training on the 100 meter  sprint for FIK UNM students. While the purpose of this study was to find out whether there was an effect of implementing circuit training on the 100-meter sprint for FIK UNM students. The type of research that would be used in this study was quantitative descriptive analysis. In this research design, research subjects were selected by purposive sampling based on certain characteristics. , research so that research subjects are homogeneous. While data analysis using SPSS 21 by using descriptive test, normality test and hypothesis test. Based on the results of the analysis of the data obtained with the title the effect of implementing circuit training on the 100-meter sprint, FIK UNM students obtained an average value of 14.7620 and obtained a P value of 0.000 (P <0.05), the data after the effect of implementing circuit training on running 100 meter sprint for FIK UNM students obtained an average score of 12.9953 and obtained a P value of 0.000 (P <0.05). and it was also seen that there was an effect of applying circuit training to the 100 meter sprint for FIK UNM students with a difference of 1.76667. While the samples that were not given the circuit training treatment obtained data values before the application of circuit training to the 100-meter sprint for FIK UNM students obtained an average value of 14.8540 and obtained a P value of 0.000 (P <0.05). And data after without the application of the circuit training for the 100 meter sprint for FIK UNM students obtained an average value of 13.5400 and obtained a P value of 0.000 (P <0.05). It can also be seen that there was an effect of applying circuit training to the 100 meter sprint for FIK UNM students with a difference of 1.31400